Technological gap in adoption of recommended practices of maize cultivation among the farmers of Buldana district in Vidarbha - - M. K Rathod; J. Ni. Jayabhaye (Journal of Agricultural Extension Management, 2015)
This study was conducted in Buldana district of Vidarbha region. The data was collected, from 120 maize growers with the help of a pretested and structured interview schedule, regarding the actual adoption of recommended practices of maize cultivation and constraints faced by them in adoption. On analysis of data, the major technological gap was found in adoption of recommended varieties of maize, use of bio-fungicide, fungicides. Bio-fertilizers and their proper rate in seed treatment, intercropping, use of weedicides and its doses, intercropping and plant protection. Overall 42.51 per cent technological gap index in maize cultivation was recorded in the study area. The major constraints in adoption of recommended practices were lack of knowledge, non availability of recommended varieties, high cost of seed and fertilizers, uncertainty in rain, unavailability of labour, non availability of FYM. Irrigation facilities etc.